Handbook of research on technologies and systems for e-collaboration during global crises - Zhao, Jingyuan; Kumar, V Vinoth (IGI Global, 2022)
"This book focuses on emerging technologies and systems, strategies and solutions for e-collaboration especially highlighting the importance of technologies and systems for e-collaboration in dealing with emerging crisis such as unpredicted pandemic diseases like COVID -19.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Business enterprises -- Computer networks; Business networks; Communication -- Technological innovations; Organizational change; COVID-19 (Disease) -- Economic aspects